Influence of Service Quality on the Decision to use Fortune Predestination Business of Users in Bangkok - Waraphat, Karin; Aphiwatpisan, Nathapat (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
The purposes of this research were to: 1) study the level of service quality, 2) study the level of decisions to use fortune predestination business of users in Bangkok; and 3) Study Influence of service quality on the decision to use fortune predestination business of users in Bangkok. The sample group consisted of 400 users of fortune predestination business in Bangkok, selected by using accidental random sampling. The research instrument was a questionnaire. The data were analyzed by using mean, standard deviation and multiple regression analysis. The results showed that: 1) the users’ had opinion service quality at a high level, and the level of decisions to use fortune predestination business of users gave the highest level was process, next were people, physical evidence, product and service, place, promotion and price; and 2) The Service quality: empathy, responsiveness, tangibles, assurance and reliability affecting decisions to use fortune predestination business of users in Bangkok with predictive power of 61.5 percent.